Development through Radio - Sibanda, Jennifer (Technical Centre for Agricultural and Rural Cooperation, 2002)
Development through Radio (DTR) is a unique rural radio project in Zimbabwe. Popularly known as the Radio Listeners´ Clubs, the DTR project was developed to give rural people access to radio. Groups of women are tr